Consumer Preference and Quality of Sachet Water Sold and Consumed in the Sunyani Municipality of Ghana. (6th August 2020) - Addo, Henry Ofosu; Amegah, Kingsley Ebenezer; Xonam, Thelma Arko; Kabenlah, Eunice; Ameyaw, Charity; Graham, Linda Obema; Tobigah, Theresa; Hammond, Barbara; Maxwell, Dorcas; Bimi, Langbong
Abstract : Good quality water is odourless, colourless, and free from faecal pollution, and a satisfactory safe supply must be made available to consumers. The study assessed consumer preference and quality of sachet water sold and consumed in the Sunyani Municipality of Ghana. A cross-sectional study design was used, and data were collected using a structured questionnaire from a sample size of 500 respondents. A total of twenty (20) samples of sachet water commonly sold and consumed in the Sunyani Municipality were also collected and analyzed for bacteriological and physicochemical parameters. Out of these 20 samples, 10 samples of sachet water were collected from the production site and the other 10 samples from the market site. Results showed that respondents' choice of sachet water was based on several indicators. While 70% (350/500) of consumers indicated that sachet water had taste, 58% (290/500) of them were not enthused when the water had colour. Using smell as an indicator, 71% of consumers have had an experience with sachet water smell being questionable. Water taste (p < 0.001 ), colour of water (p < 0.001 ), smell (p < 0.001 ), and increase in cost (p < 0.001 ) were found as determinants of consumer preference. Consumers who said the colour of water informed their decision when buying sachet water were seven times more likely to have a preference for a particular brand (OR 7.057, CI: 4.474–11.133). Those who checked for expiry dates when buying water (OR 4.871, CI: 3.110–7.628) and those who looked out for Food and Drugs Authority stamp (OR 4.433, CI: 2.806–7.003) were both four times more likely to have a preference for a particular brand. Water quality tests also indicated that 30% of all water samples collected from the production site were contaminated with total coliforms and 50% of sachet water samples collected from the markets were also contaminated with coliforms. The same brands of sachet water that contained total coliforms from the production site were the same brands that contained total coliforms selected from the market. From this study, only total coliforms other than Escherichia coli were detected in the water samples analyzed. It was observed that the evaluated physicochemical parameters of the water analyzed were within the accepted WHO limits. It is recommended that consumers be educated about the indicators to look out for when buying sachet water and, also, that regulatory bodies be empowered to ban the sale of unwholesome brands of sachet water on the market.